L’IMPACT DES NORMES IFRS SUR LE CONTENU INFORMATIONNEL DES ÉTATS FINANCIERS DES PME COTÉES DANS LE CONTEXTE FRANÇAIS - Salameh, Elie (European Scientific Journal, ESJ, 2013)
This study is aimed at determining whether IFRS compliance by listed SMEs in France leads to accounting data that are more relevant and comparable than those produced by adopting local accounting standards. This paper conveys further evidence on these two attributes of accounting information over the period 2002-2007, using association studies methodology. Moreover, firm-specific factors are incorporated to isolate the effect of IFRS adoption. The results obtained show that there has been an improvement in the value relevance of financial reporting. In the other hand, local comparability is adversely affected if both IFRS and local accounting standards are applied at the same time in France.